Theory of change for the dairy value chain in Ethiopia, developed for the CGIAR Initiative Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion - Mekuriaw, Zeleke; Meseret, Selam; Temesgen, Wudu; Derseh, Melkamu; Marshall, Karen; Baltenweck, Isabelle (International Livestock Research Institute, 2024)
The CGIAR Initiative Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING) is an initiative that focuses on sustainable animal productivity. This initiative aims to contribute to transforming livestock sectors in target countries to make them more productive, resilient, equitable and sustainable (see Box 1 on how this objective will be achieved). The initiative is working in seven countries located in East Africa (Ethiopia, Kenya, Tanzania, and Uganda), West Africa (Mali), Southeast Asia (Vietnam) and South Asia (Nepal) and works on 15 livestock value chains in total.